Master of the age : an Islamic treatise on the necessity of the imamate : a critical edition of the Arabic text and English translation of Ḥamīd al-Dīn Aḥmad b. ʻAbd Allāh al-Kirmānī's al-Maṣābīḥ fī ithbāt al-imāma /: an Islamic treatise on the necessity of the imamate : a critical edition of the Arabic text and English translation of Ḥamīd al-Dīn Aḥmad b. ʻAbd Allāh al-Kirmānī's al-Maṣābīḥ fī ithbāt al-imāma. (2007) - Unknown
No abstract available